Método constructivo de vías en áreas protegidas en la región costa - Orellana Gutiérrez, Edgar Daniel (2022)
In this research work, satisfaction among road users in protected areas of the coastal region was related to the prevailing design and construction criteria and standards in the country. The aim was to establish whether the design standards and construction procedures in force in common roads in Ecuador can be applied to roads in protected areas on the Ecuadorian coast, guaranteeing sustainability and visitor satisfaction. The applied methodology has a quantitative approach with a descriptive scope, deductive method, observation technique and documentary bibliography. To solve the problem, the current regulations based on the MTOP regulations were established, for which the access road to the Manglares Chuture Ecological Reserve, located on the Ecuadorian coast, in the province of Guayas, was analyzed as a study area. Design parameters such as horizontal, vertical, pavement, hydraulic and signage will be changed, making the necessary calculations for a traffic design period of 20 years………